2002
DOI: 10.1007/bf03179833
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of resting energy expenditure in obese and non-obese children and adolescents

Abstract: Resting energy expenditure (REE) is the largest component of total daily energy expenditure. Objectives of this study were to examine whether differences in REE exist after obesity develops in a group of children and adolescents, and to determine the effects of body composition, gender, age, pubertal development and parental obesity on REE. In 116 Caucasian children and adolescents (57 obese and 59 non-obese), aged 7.8 to 16.6 years, REE was assessed by open-circuit indirect calorimetry and different anthropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 30 publications
(41 reference statements)
2
19
2
2
Order By: Relevance
“…The failure to detect differences may be due to the small sample size tested. The average REE in this study, measured using breath-by-breath analysis, was higher than the 22–26 kcal/kg per day reported for studies of obese children measured using a head canopy in which exhaled air from multiple breath cycles was intermingled and sampled (30,33). The measured REE for 7–8 y youth was lower than normal-weight values (boys/girls) of 51/44 kcal/kg per day for 3–8 y (1), which was expected since the comparison group included younger children who have higher metabolic rates.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…The failure to detect differences may be due to the small sample size tested. The average REE in this study, measured using breath-by-breath analysis, was higher than the 22–26 kcal/kg per day reported for studies of obese children measured using a head canopy in which exhaled air from multiple breath cycles was intermingled and sampled (30,33). The measured REE for 7–8 y youth was lower than normal-weight values (boys/girls) of 51/44 kcal/kg per day for 3–8 y (1), which was expected since the comparison group included younger children who have higher metabolic rates.…”
Section: Resultscontrasting
confidence: 76%
“…Mean REE was nearly that of normal-weight values (boys/girls) of 37/33 kcal/kg per day for 9-13 y and 29/25 kcal/kg per day for 14–18 y (1). Weight-adjusted REE was expected to be lower for obese individuals than for healthy-weight children (28,30,33) because fat tissue is substantially less metabolically active than LBM, and fat mass contributes proportionately more to the total body weight in obesity. To our knowledge, only one study tested differences in REE (24-hour kcal/kg total body weight) as a factor of obesity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure to find an increase in RMR following fish oil treatment is hard to explain given the significant increase in lean mass observed in the present study. Several studies have shown that lean mass is the largest determinant of RMR [28-30], and decreasing lean mass decreases RMR [31], while increasing lean mass increases RMR [32]. Therefore, it would be expected that the increase in lean mass would correspond to an increased RMR following fish oil treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The main significant determinant of BMR is FFM (R 2 = 0.65-0.80 [24,25]), whereas FM is significant only in obese subjects (R 2 < 0.04, [24,26]). Sex is also a significant determinant of BMR (0.02 < R 2 < 0.04, [24]): after adjustment for body composition, BMR is significantly higher in boys than in girls, by 3% and 6% in prepubertal and pubertal subjects, respectively [24,27,28], because of (1) higher proportions of skeletal glycolytic fibres [29], and higher Na + -K + ATPase activity [30], and (2) changes in hormonal status [19].…”
Section: Basal Metabolic Ratementioning
confidence: 98%